Iron-catalyzed cross-dehydrogenative C–H amidation of benzofurans and benzothiophenes with anilines. Issue 7 (4th February 2021) - Ni, Yang; Wan, Xiang; Zuo, Honghua; Bashir, Muhammad Adnan; Liu, Yu; Yu, Huaibin; Liao, Rong-Zhen; Wu, Guojiao; Zhong, Fangrui
Abstract : An efficient iron-catalyzed radical cross-dehydrogenative aromatic C–H amidation provides a straightforward access to structurally diverse diarylamine derivatives incorporating benzofuran/benzothiophene motifs. Abstract : An efficient iron-catalyzed cross-dehydrogenative aromatic C–H amidation using DDQ as an oxidant under mild conditions is reported, providing a straightforward access to structurally diverse diarylamine derivatives incorporating benzofuran/benzothiophene motifs. Mechanistic studies indicated that a nitrogen-centered anilino radical is involved in the C–N bond formation.